2013
DOI: 10.1016/j.schres.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, diagnostic specificity and genetic liability for context-processing deficits in schizophrenia

Abstract: Context-processing deficits have been shown in schizophrenia during first-episode, medication-naïve status, that persist after short-term antipsychotic treatment and also in first-degree relatives of individuals with schizophrenia. To confirm longer term persistence of deficits, we examined schizophrenia patients (n=63) during first-episode, medication-naïve status through to one-year follow-up, compared to healthy control (n=83) and non-schizophrenia psychosis comparison (n=47) groups, as well as unaffected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 34 publications
6
21
0
Order By: Relevance
“…2,5,[7][8][9]11,13,22 Rather, we observed that the schizophrenia and schizoaffective disorder groups had comparable false alarm rates on BX and AY trials, while bipolar proband and control groups demonstrated higher false alarm rate on AY trials. These findings suggest that impaired performance on expectancy tasks in schizophrenia and schizoaffective disorder are not attributable to impaired context processing per se, and that patients with bipolar disorder have greater difficulty on expectancy tasks due to deficits in response inhibition, consistent with findings of inhibitory deficits among this group.…”
Section: -21mentioning
confidence: 50%
See 1 more Smart Citation
“…2,5,[7][8][9]11,13,22 Rather, we observed that the schizophrenia and schizoaffective disorder groups had comparable false alarm rates on BX and AY trials, while bipolar proband and control groups demonstrated higher false alarm rate on AY trials. These findings suggest that impaired performance on expectancy tasks in schizophrenia and schizoaffective disorder are not attributable to impaired context processing per se, and that patients with bipolar disorder have greater difficulty on expectancy tasks due to deficits in response inhibition, consistent with findings of inhibitory deficits among this group.…”
Section: -21mentioning
confidence: 50%
“…2,[7][8][9][10][11] Findings of impaired context processing among unaffected relatives 9,12,13 and among those with schizoptypal personality disorder have also been reported, 14 suggesting that impairment in this ability may represent an endophenotype for schizophrenia.…”
Section: Introductionmentioning
confidence: 98%
“…The robust changes that have been detected using CPTs have lead to the suggestion that CPT deficits could be considered an endophenotype of schizophrenia, fitting the Gottesman and Gould (2003) criteria (Gottesman and Gould, 2003;Gur et al, 2007). The CPT protocol has been widely used with results robustly demonstrating deficits in people with schizophrenia and first-degree relatives (Snitz et al, 2006;Delawalla et al, 2008;MacDonald, 2008;Richard et al, 2013). Deficits have been shown to be stable from before first-episode of psychosis, during medication and remission, and performance errors do not correlate with psychotic symptoms in non-schizophrenia patients experiencing psychosis (Snitz et al, 2006;Richard et al, 2013).…”
Section: Rodent Models Of Schizophreniamentioning
confidence: 99%
“…The CPT protocol has been widely used with results robustly demonstrating deficits in people with schizophrenia and first-degree relatives (Snitz et al, 2006;Delawalla et al, 2008;MacDonald, 2008;Richard et al, 2013). Deficits have been shown to be stable from before first-episode of psychosis, during medication and remission, and performance errors do not correlate with psychotic symptoms in non-schizophrenia patients experiencing psychosis (Snitz et al, 2006;Richard et al, 2013). Together these findings suggest that deficits on CPT are at the foundations of this disorder.…”
Section: Rodent Models Of Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation